2012
DOI: 10.1111/j.1469-8137.2012.04240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of population size and isolation on heterosis, mean fitness, and inbreeding depression in a perennial plant

Abstract: Summary• In small isolated populations, genetic drift is expected to increase chance fixation of partly recessive, mildly deleterious mutations, reducing mean fitness and inbreeding depression within populations and increasing heterosis in outcrosses between populations.• We estimated relative effective sizes and migration among populations and compared mean fitness, heterosis, and inbreeding depression for eight large and eight small populations of a perennial plant on the basis of fitness of progeny produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 87 publications
(160 reference statements)
2
85
0
1
Order By: Relevance
“…Both populations are small and are geographically isolated in islands, where genetic drift can increase the fixation of deleterious alleles and outcrosses may be carried out between related parents. Therefore, reduced individual fitness and increased inbreeding depression can be expected in both populations (Kimura, Maruyama, & Crow, 1963; Lynch & Gabriel, 1990; Oakley & Winn, 2012). However, these populations are located at the dry edge of the species’ distribution range, and strong selection pressures related to water availability may be selecting drought‐adapted phenotypes, as has been suggested for marginal populations of other species (Kirkpatrick & Barton, 1997; Lesica & Allendorf, 1995), including Tertiary relicts such as Ramonda myconi (Muller et al., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Both populations are small and are geographically isolated in islands, where genetic drift can increase the fixation of deleterious alleles and outcrosses may be carried out between related parents. Therefore, reduced individual fitness and increased inbreeding depression can be expected in both populations (Kimura, Maruyama, & Crow, 1963; Lynch & Gabriel, 1990; Oakley & Winn, 2012). However, these populations are located at the dry edge of the species’ distribution range, and strong selection pressures related to water availability may be selecting drought‐adapted phenotypes, as has been suggested for marginal populations of other species (Kirkpatrick & Barton, 1997; Lesica & Allendorf, 1995), including Tertiary relicts such as Ramonda myconi (Muller et al., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Many mildly deleterious recessive or nearly recessive mutations are predicted to become fixed when effective population sizes are modest and gene flow is limited (Whitlock et al, 2000). Heterosis in F 1 crosses between natural populations is ubiquitous (for example, Fenster, 1991;Armbruster et al, 1997;Edmands, 1999;Oakley and Winn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced pollinator visitation has been observed at low density in this species (Boyle and Menges 2001), which could select for increased autogamous selfing as a means of reproductive assurance. Although the short-term selective advantage of autogamy could be diminished by inbreeding depression (reviewed in Goodwillie et al 2005), inbreeding depression in this species has been shown to be not significantly different from zero and averages less than 28% (Oakley and Winn 2012).…”
Section: Study Systemmentioning
confidence: 98%
“…Previous work strongly implicates a role of genetic drift in shaping genetic variation related to fitness in small populations. Heterosis in crosses between small populations (Oakley and Winn 2012) suggests the fixation of partly recessive deleterious mutations within populations, which cannot be attributed to natural selection. The habitat requirements and demography of this species have also been well studied (Quintana-Ascencio and Morales-Hernandez 1997; QuintanaAscencio et al 1998QuintanaAscencio et al , 2003QuintanaAscencio et al , 2007, permitting identification of phenological and morphological traits likely to affect fitness in this species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation